INFLUENCE OF HUMAN CAPITAL MANAGEMENT AND CHARACTERISTICS OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT PT. BANK SUMUT SYARIAH MEDAN, KATAMSO BRANCH - Citra, Shavira Puspita; DIrbawanto, Nana Dyki (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
This study aims to determine how the influence of Human Capital Management on Employee Performance PT. Bank SUMUT Syariah Medan Katamso Branch, analyzed the influence of Organizational Culture Characteristics on Employee Performance of PT. Bank SUMUT Syariah Medan Katamso Branch and analyze the influence of Human Capital Management and Organizational Culture Characteristics Performance of PT. Bank SUMUT Syariah Medan Katamso Branch. This research uses quantitative research methods. The population in this study were employees of PT. Bank SUMUT Syariah Medan Katamso Branch with samples taken as many as 30 respondents. The sampling technique in this research is purposive sampling. The data collection method used a questionnaire method which was measured using a Likert scale. The analytical method used in this study is the classical assumption test, multiple linear regression analysis, multiple correlation analysis, and hypothesis testing using SPSS. The results of this study indicate that Human Resource Management and Organizational Culture have an effect on employee performance. Based on the results of the determination test, the Adjusted R Square value of 0.547 means 54.7%, so it can be concluded that there is a direct relationship between the variables of Human Capital Management, Organizational Culture Characteristics, and Performance Personnel. R Square value of 0.578 (57.8%) the independent variables of Human Capital Management and Organizational Culture Characteristics simultaneously have an effect of 57.8% on the dependent variable, namely Employee Performance, while the rest is influenced by other variables not examined in this study.